Implementasi Pembelajaran Berpusat Pada Peserta Didik Oleh Calon Guru Penggerak Melalui Bimbingan Guru Praktisi - Mahmud, Amran; Syukurman (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2024)
This research aims to explore the role of practitioner teachers in improving the quality of prospective Class 4 driving teachers in Bima Regency, especially in the context of learning that supports students. This research uses a qualitative approach with data collection techniques through in-depth interviews, observation, and document analysis. The main respondents were practitioner teachers who were involved in the learning of prospective teacher candidates for Class 4. The findings of this research illustrate the key role of practitioner teachers in designing and implementing effective learning, supporting the development of prospective teachers' pedagogical skills, and ensuring learning experiences that benefit students. The implications of the results of this research can be used as a basis for related parties to improve the quality of learning for prospective teachers to achieve better educational goals in Bima Regency.